1982
DOI: 10.1161/01.cir.65.4.690
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of left ventricular pressure during isovolumic relaxation in coronary artery disease.

Abstract: SUMMARY When a decrease in left ventricular isovolumic pressure is considered as an exponential, the rate of relaxation can be defined by a time constant (T). Previously, T has been calculated from the slope of In (pressure) against time, but this method is valid only when the asymptote of the exponential is zero. In this study two estimates of T were made: Tin from the slope of In (pressure) against time, and TEXP by a method of exponential analysis that also estimated the asymptote. These techniques were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Time to 50% pressure decline was not calculated, since this index is unreliable when developed pressure changes significantly (2). (10)(11)(12), large animal models (3), and isolated perfused hearts (7)(8)(9). However, previous studies in isolated perfused hearts studied only mild reductions of coronary flow to 50% (8) and 33% (7) cline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Time to 50% pressure decline was not calculated, since this index is unreliable when developed pressure changes significantly (2). (10)(11)(12), large animal models (3), and isolated perfused hearts (7)(8)(9). However, previous studies in isolated perfused hearts studied only mild reductions of coronary flow to 50% (8) and 33% (7) cline.…”
Section: Methodsmentioning
confidence: 99%
“…The most reliable and least load-dependent index ofmyocardial relaxation is the time constant of left ventricular pressure decline (Tp)I (2)(3)(4). Several studies have documented an increase of rp during ischemia in a variety of experimental preparations (5)(6)(7)(8)(9) and patients with coronary artery disease (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…In their study, PB showed a significant change only in patients who developed myocardial ischemia with exercise. Thompson et al 42 showed a similar wide range of variation in resting values for PB and point out that the relevance of PB to diastolic relaxation after mitral valve opening is uncertain. Since the physiologic meaning of PB is unclear, we cannot interpret its failure to change consistently with milrinone in this study.…”
mentioning
confidence: 91%
“…We calculated the relaxation time constant with Thompson's method ( bf ) from exponential analysis [P(t) = (P0 -P∞) exp (-t / bf ) + P∞]. 19,20 Fitting was done from the time of the peak negative LV dP/dt to the time at which LV pressure had fallen to 5 mmHg above the succeeding end-diastolic pressure (EDP). Correlation coefficients of the exponential fittings of all the beats were more than 0.99 by this method in all the patients.…”
Section: Discussionmentioning
confidence: 99%